Study of the Level of Pro- and Antiangiogenic Growth Factors in Vitreous Fluid in Neovascular Age-Related Macular Degeneration on the Background of Treatment - M. M. Arkhipova; V. G. Likhvantseva; A. S. Gevorgyan; S. I. Rychkova; S. A. Selkov (Oftalʹmologiâ)
Purpose: to study the level of pro- and antiangiogenic growth factors in the vitreous fluid of the eyes with the neovascular form of agerelated macular degeneration (nAMD) against the background of antiangiogenic therapy.Patients and methods. The concentration of proangiogenic (IL-8, angiogenin, TNF-α, VEGF, bFGF) and antiangiogenic (IFN-α, TGF-β IFN-γ) growth factors in the vitreous fluid of nAMD patients was determined by multiplex flow cytometry. Patients with senile cataracts without signs of AMD and cataract patients burdened with naïve (untreated) nAMD were in the comparison groups.Results. Compared with senile cataracts, proangiogenic cytokines TNF-α were present more frequently and at a higher level in the vitreous fluid of the eyes with treated nVMD (75 % vs. 47.5 %, p < 0.05; Msr ± m: 2.4 ± 0.5 vs. 1.4 ± 0.3 pg/ml, p < 0.05), IL-8 (100 % vs. 75 %, p < 0.01; 492.9 ± 75.7 vs. 8.5 ± 1.5 pg/ml, p < 0.01), angiogenin (3822.4 ± 498.6 vs. 2820.2 ± 319.3, p < 0.01) and FGFb (58.3 % vs. 26.7 %, p < 0.05; 10.1 ± 5.9 vs. 2.7 ± 1.0, p < 0.01). In both groups of patients, antiangiogenic factors IFN-γ and TGF-β were practically not detected, but the concentration of IFN-α was significantly higher (6.4 ± 1.7 versus 4.4 ± 0.4, p < 0.01). VEGF levels in both nosological groups were almost identical: 17.5 ± 14.0 (with nAMD) versus 18.4 ± 3.2 (n/a), while VEGF was found in vitreous fluid in the cataract group significantly more often (68.2 % vs. 17 %, p < 0.01). By way of explanation, the authors suggested that since patients with nAMD had previously been administered the anti-angiogenic drug Ranibizumab, it is possible that the VEGF production was under the control of the drug, that is, suppressed or blocked.Conclusion. Elevated levels of proangiogenic growth factors IL-8, angiogenin, TNF-α and bFGF in vitreous fluid with nAMD against the background of antiangiogenic therapy with ranibizumab suggest the presence of other, independent of VEGF, acting mechanisms for stimulating angiogenesis. The absence of antiangiogenic growth factors IFN-γ and TGF-β in the vitreous fluid allows us to think about the presence of a defect in the control and regulation of angiogenesis in nAMD. The rare detection of VEGF in combination with a significant decrease in its concentration compared to senile cataracts against the background of treatment with ranibizumab of the eyes with nAMD demonstrates targeted inhibition in practice. Against the background of treatment with angiostatic drugs, an inversion of the angiogenic phenotype occurs with the formation of new workarounds of angiogenesis, which apparently dictates the connection of drugs with other mechanisms of action.